2021
DOI: 10.3390/microorganisms9030581
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica—Gut Microbiota Interaction: More Than Meets the Eye

Abstract: Amebiasis is a disease caused by the unicellular parasite Entamoeba histolytica. In most cases, the infection is asymptomatic but when symptomatic, the infection can cause dysentery and invasive extraintestinal complications. In the gut, E. histolytica feeds on bacteria. Increasing evidences support the role of the gut microbiota in the development of the disease. In this review we will discuss the consequences of E. histolytica infection on the gut microbiota. We will also discuss new evidences about the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 101 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…An increasing number of studies support an intricate relationship between the gut microbiota and E. histolytica ( Burgess and Petri, 2016 ; Ankri, 2021 ) and significant changes in the gut microbiota has been associated with amebiasis ( Rani et al, 2006 ; Verma et al, 2012 ). For example, the presence of Prevotella copri , in gut flora was associated with E. histolytica induced diarrheal disease in children ( Ngobeni et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies support an intricate relationship between the gut microbiota and E. histolytica ( Burgess and Petri, 2016 ; Ankri, 2021 ) and significant changes in the gut microbiota has been associated with amebiasis ( Rani et al, 2006 ; Verma et al, 2012 ). For example, the presence of Prevotella copri , in gut flora was associated with E. histolytica induced diarrheal disease in children ( Ngobeni et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut bacteria is associated with unique combinations that are influenced by the physiological conditions within the intestine; most of these are commensal ( Lynch and Pedersen, 2016 ). Trophozoites feed on gut bacteria, and the bacteria are able to influence the virulence of E. histolytica (for a recent review see Ankri, 2021 ). As an example, cultivating E. histolytica with E. coli O55 can boost E. histolytica ’s virulence which depends on contact between the amoeba and bacteria ( Bracha and Mirelman, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we demonstrated that AF triggers OS inside E. histolytica trophozoites, resulting in the oxidation of more than 500 proteins, including many redox enzymes that are essential for controlling the intracellular levels of ROS in the parasite [ 28 , 42 , 43 ]. Here, we characterized E. histolytica trophozoites that were adapted to 2 µM AF.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we have demonstrated that AF triggers OS inside E.histolytica trophozoites resulting in the oxidation of more than 500 proteins including many redox enzymes which are essential for maintaining intracellular levels of reactive oxygen species in the parasite [28,43,44]. Here, we have characterized E.histolytica trophozoites that have been adapted to 2 μM AF.…”
Section: Discussionmentioning
confidence: 99%